Menkes’ kinky hair syndrome. Report of a Norwegian family. - Selvaag, E. (European Journal of Pediatric Dermatology, 1999)
A two-year old boy with mental retardation, seizures, and pili torti is presented. Copper analyses showed low values, consistent with the diagnosis of Menkes’ disease. The scanning electron microscopic investigation of the hairs showed typical pili torti, namely twisting of hairs. The scanning electron microscopic investigation of the hairs from his close relatives showed twisting of hairs in one of his sisters, and ridges and grooves in the hairs from his mother. DNA analyses showed a single base-pair mutation in the boy, which also was seen in his mother and one of his two maternal aunts, indicating a carrier status in these female relatives.